Socioeconomic, cultural and attitudinal determinants of female marriage timing - Deano, Angelito M. 1944- (Quezon City Population Institute, University of the Philippines, Diliman, 1985)
Using data on ever-married women in the three pre-selected strata (rural), lower urban and middle urban) in central Luzon and Metro Manila derived from the 1978 Asian Marriage Survey, the determinants of marriage timing were examined. Socioeconomic, cultural and attitudinal variables were ascertained using crosstabulation and multiple regression analyses.
Generally, a number of background variables were opted to be significantly correlated with women's age at first marriage. The significance of the variables was found to be important for a particular group of women (by marriage cohort) and for a particular place of residence.
Crosstabulation anlaysis yielded mother's occupation at time of respondent's marriage, land ownership of parents, parental social status, respondent's education. woman's occupation before marriage, engagement, marriage ritual;s, religiosity and readiness to marry to be significantly associated with the timing of marriage.
Multivariate analysis showed that in each stratum, different sets of predictors emerged. In the rural stratum, education, mother's survival before respondent's marriage and courtship were significant predictors of marriage timing. In the lower urban stratum (squatter area), more cultural variables turned out to be strong predictors -- engagement, marriage consummation, courtship and marriage rituals.
Education and premarital occupation were the only important socioeconomic determinants. In contrast with the squatter area, the determinants of age at marriage in the middle urban stratum were more socioeconomic where all were found to be strong predictors. The only two cultural variables that emerged to be important were courtship and religiosity.
A comparison of the results of this study with previous studies yielded consistencies in some of the findings. It has been hypothesized that such inconsistencies may be due to differences in methodology, the sample under study, and the inclusion of attitudinal variables. It has been shown that the net effects of socioeconomic and cultural predictors were better identified when attitudinal variables which were highly associated with age at marriage were controlled.
Vita.
Thesis
Keywords: Marriage -- Philippines -- Manila metropolitan area; Marriage -- Philippines -- Central Luzon; Women -- Philippines